2017
DOI: 10.1111/ans.13869
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of two surgical approaches for calcaneal fractures: sinus tarsi versus extensile lateral approach

Abstract: The existing evidence supports STA to be a better approach for treating calcaneal fractures, and this might aid in the management of this injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Previous studies comparing the therapeutic efficacy and clinical outcomes of ORIF via ELA or STA have showed no significant differences. 16,32,34,48 From our results, the clinical outcomes including the Bohler's and Gissane angle, VAS scores, AOFAS scores were in accord with previous studies. Nevertheless, to the best of our knowledge, no studies comparing the direct costs and effectiveness of two techniques in China were conducted.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies comparing the therapeutic efficacy and clinical outcomes of ORIF via ELA or STA have showed no significant differences. 16,32,34,48 From our results, the clinical outcomes including the Bohler's and Gissane angle, VAS scores, AOFAS scores were in accord with previous studies. Nevertheless, to the best of our knowledge, no studies comparing the direct costs and effectiveness of two techniques in China were conducted.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies comparing the therapeutic e cacy and clinical outcomes of ORIF via ELA or STA have showed no signi cant differences. [37][38][39][40] From our results, the clinical outcomes including the Bohler's and Gissane angle, VAS scores, AOFAS scores were in accord with previous studies. Nevertheless, to the best of our knowledge, no studies comparing the direct costs and effectiveness of two techniques in China were conducted.…”
Section: Discussionsupporting
confidence: 90%
“…The 3 typical approaches used for calcaneal osteosynthesis are the lateral approach, medial approach, and combined lateral and medial approach. We chose the lateral approach in the present study, because the extensile lateral approach has achieved wide popularity for surgical fixation by providing excellent exposure, allowing access to manipulate and fix the fracture fragments (39,40). In addition, De Groot (41) found that complications after the lateral approach for calcaneal fractures did not influence the mid-to long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%